The red, yellow and orange colours of Thai reform - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
Thailand’s constitution has undergone numerous changes in tandem with the rise and fall of a long line of political players. The shadow of instability lingers. In recent years, two opposing camps have been drawing all the attention: the “yellow” pro-monarchy camp, versus the red-shirt supporters of former prime minister Thaksin Shinawatra. According to Andrew Harding, a visiting law professor at Singapore Management University, the views of the in-betweens, the so-called “orange” camp, which represents the ordinary, nonpartisan Thai citizens, might be the way forward.